Enhancing Rail Competitiveness with Online Rail Freight Exchange. Issue 1 (January 2015) - Endemann, Peter
In many European countries, rail freight demand has increased considerably during the past 10 to 15 years though only a few countries have reached considerable levels such as those observed in the United States. A closer look at the German case reveals that, given a considerable amount of empty wagons and a nontransparent market, there is still some potential to increase efficiency and competitiveness of rail freight and to overcome knowledge and information barriers in the rail freight market. Embedded in the strategy of the transnational project titled "CODE 24" (Corridor 24 Development Rotterdam–Genoa), an online rail freight exchange appears to be the appropriate instrument to cope with these challenges. The exchange is a market platform through which rail freight services are offered and requested online. At the start of the project, except for some initial business and case studies, the market relevance of such a tool and the requirements of potential users (predominantly shipping companies, transport logistics providers, and rail operators) had yet to be explored. Therefore, a workshop was held with these groups and other experts in 2011. From the outcome, potential operators of the platform had to be identified. In September 2012, CODE 24 identified two companies that were interested in cooperating with the CODE 24 network and developing such an online rail market ready for commercialization. CODE 24 decided to support both companies and emphasize their neutrality. Both platforms have been available since October 2013 and were presented at a joint workshop with the European Union Interreg IVB Programme in November 2013. A preliminary appraisal by February 2015 showed that both platforms were working well and had up to 94 registered companies.